Perancangan Sistem Diagnosis Autisme pada Anak dengan Menggunakan Naïve Bayes - Yoannita Yoannita (Maranatha University Press, 2017)
Children with autism are characterized by symtomps and delays in cognitive fields, social interaction, and behaviors that appear before the age of three. Parents sometimes do not know if their child has autism so they do not know how to cope. It is necessary to design a diagnosys system so that parents can know and detect the autism disorder as early as possible. The classification system is using Naïve Bayes method by comparing the probability result for each three category (aloof, passive, active but odd). For Naïve Bayes's weakness is solved by add-one smoothing method so that the probability of Naïve Bayes to a target based on the existing symptoms.Keywords— Naïve Bayes, autism, add one smoothing